Lack of Impacts during Early Establishment Highlights a Short-Term Management Window for Minimizing Invasions from Perennial Biomass Crops - West, Natalie M.; Matlaga, David P.; Muthukrishnan, Ranjan; Spyreas, Greg; Jordan, Nicholas R.; Forester, James D.; Davis, Adam S. (Frontiers in Plant Science, 2017)
Managing intentional species introductions requires evaluating potential ecological risks. However, it is difficult to weigh costs and benefits when data about interactions between novel species and the communities they are introduced to are scarce. In anticipation of expanded cultivation of perennial biomass crops, we experimentally introduced Miscanthus sinensis and Miscanthus × giganteus (two non-native candidate biomass crops) into two different non-crop habitats (old field and flood-plain forest) to evaluate their establishment success and impact on ambient local communities. We followed these controlled introductions and the composition dynamics of the receiving communities over a five-year period. Habitats differed widely in adult Miscanthus survival and reproduction potential between species, although seed persistence and seedling emergence were similar in the two biomass crops in both habitats. Few introductions survived in the floodplain forest habitat, and this mortality precluded analyses of their potential impacts there. In old field habitats, proportional survival ranged from 0.3-0.4, and plant survival and growth increased with age. However, there was no evidence of biomass crop species effects on community richness or evenness or strong impacts on the resident old-field constituents across five years. These results suggest that Miscanthus species could establish outside of cultivated fields, but there will likely be a lag in any impacts on the receiving communities. Local North American invasions by M. sinensis and M. sacchariflorus display the potential for Miscanthus species to develop aggressively expanding populations. However, the weak short-term community-level impacts demonstrated in the current study indicate a clear management window in which eradicating species footholds is easily achieved, if they can be detected early enough. Diligent long-term monitoring, detection, and eradication plans are needed to successfully minimize harmful invasions from these biomass crops.